Evaluasi Sikap Belajar Daring Mahasiswa Prodi Pendidikan Biologi - Inda Puspita Sari; Syukri Hamzah (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to describe the online learning attitude of students of the Biology Education Study Program, PGRI Silampari University Class of 2021-2022. The method used is a case study. The research data are in the form of interviews and questionnaires given to students of class 1.A Biology Education Study Program. The data analysis techniques of this research include data reduction, data display and conclusion drawing. The results showed that the highest score in the small group test response data related to student attitudes about online learning was 81.25%. In conclusion, the student's learning attitude in the Biology Education study program at PGRI Silampari University is good. Keywords: Learning, Online, Evaluation, Attitude